Impingement jets on a confined assembly of rotating hot cylinder covered by a surface porous layer - Ismael, Muneer A.; Younes, Obai; Fteiti, Mehdi A.; Ghalambaz, Mohammad; Homod, Raad (Applied thermal engineering)
Thermal stresses encountered in the production of steel rod is a challenging problem arising from the irregular temperature distribution along the circumference of the rod. This study investigates the cooling process of a hot cylinder with a uniform surface temperature. The concept of the problem is a rotating cylinder immersed in an annular porous medium under the impact of two impinging jets. The jets are confined and act upward and downward. The rotational speed of the cylinder, the eccentricity of the surface porous layer and its Darcy number and Reynolds number are varied to organize the feasibility of the suggested problem. The parameters are controlled to be within the laminar mathematical system, which is solved computationally using the finite element method. The results show a promising role of the porous surface layer as it raises the Nusselt number, where it elevates 78% greater than a bared cylinder for a Darcy number Da = 10−2 and a Reynolds number Re = 400. It was found that although the rotation of the cylinder reduces the Nusselt number, it contributes highly to the uniformity of the surface temperature of the cylinder. It was found also that the eccentricity of the porous layer increases the average Nusselt number by 28% for Re = 300 and Da = 10−2. The porous layer and the cylinder rotation increase slightly the pressure drop.